An Implementation of blood Glucose and cholesterol monitoring device using non-invasive technique - Shubha B; Anuradha M G; Poornima N; Suprada H S; Prathiksha R V (EMITTER International Journal of Engineering Technology, 2023)
Invasive testing of glucose and cholesterol levels in the blood is the most prevalent procedure, which is uncomfortable, expensive, and risky since it can spread infections and harm skin cells. Diabetes and cholesterol are two of the most common diseases in the world, and they require constant monitoring to avoid health issues and organ damage. As a result, a non-invasive approach will allow for more regular testing and painless monitoring. The blood glucose and cholesterol levels can be assessed using the principle of reflecting and refractive properties of NIR light source against blood components. The MAX30100 sensor circuit gives SPO2 (Saturated Peripheral Oxygen Level) and BPM (beats per minute, or heart rate) information to the regression model, which is used to forecast blood glucose and cholesterol levels. The polynomial regression model is trained using preset datasets, and the trained model yields regression co-efficient values. For the fresh sample inputs from the sensor, the co-efficient values are used to estimate the new needed parameter value. The projected blood glucose and cholesterol levels are displayed on the LCD Display and delivered through Bluetooth HC-05 module via Serial communication to the mobile application.